2015
DOI: 10.1002/anie.201504839
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurement of Transmitters in Individual Vesicles in the Cytoplasm of Single Cells with Nanotip Electrodes

Abstract: Quantification of vesicular transmitter contents is important for studying the mechanisms of neurotransmission and malfunction in disease and yet it is incredibly difficult to measure the small contents of neurotransmitters in the attoliter volume of a single vesicle, especially in the cell environment. We introduce a novel method, intracellular vesicle electrochemical cytometry. A nano-tip conical carbon fiber microelectrode is used to electrochemically measure the total contents of electroactive neurotransmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
301
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 280 publications
(314 citation statements)
references
References 33 publications
9
301
2
2
Order By: Relevance
“…This value was slightly higher than the previously reported value of 114,300 ± 2105 dopamine molecules 30 and lower than 194,000 ± 13,000 reported by Colliver et al 12 Control PC12 vesicles probed intracellularly contained an average of 152,900 ± 8920 molecules, also higher than previously reported 114,500 ± 15,300 value. 10 In both cases, the difference in measured dopamine content compared with previously reported values might be attributed to differences in culturing and/or experimental conditions. However, we consistently found that the amount released was lower than the amount measured intracellularly in agreement with the concept of partial release.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…This value was slightly higher than the previously reported value of 114,300 ± 2105 dopamine molecules 30 and lower than 194,000 ± 13,000 reported by Colliver et al 12 Control PC12 vesicles probed intracellularly contained an average of 152,900 ± 8920 molecules, also higher than previously reported 114,500 ± 15,300 value. 10 In both cases, the difference in measured dopamine content compared with previously reported values might be attributed to differences in culturing and/or experimental conditions. However, we consistently found that the amount released was lower than the amount measured intracellularly in agreement with the concept of partial release.…”
Section: Resultsmentioning
confidence: 75%
“…The transmitter release upon stimulation was measured with single cell amperometry, 23 whereas dopamine vesicle content was determined with a newly developed technique called intracellular vesicle electrochemical cytometry. 10 Imaging Chemical Content of Single Vesicles by NanoSIMS. We began by chemically imaging the 13 Cdopamine content of LDCVs in PC12 cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations